Peranan kursus pengajian umum dalam pembangunan kemahiran insaniah: pengalaman UiTM - Muhamad Rahimi Osman, (Universiti Kebangsaan Malaysia, 2010)
Graduate employability has become a national issue as unemployment among them has increased due to the economic crisis. The main factor influencing graduate unemployability is the mismatch between their skills and the industry needs. The employer are not looking for candidates with just paper qualification, but also soft skills which include communication skills, leadership and teamwork, problem solving and scientific thinking, management skills and entrepreneurship besides ethical values and professionalism. Thus, higher education cirrriculum must emphasize the development of soft skills to generate profesional human capital. This article elaborates on Universiti Teknologi MARA implementation of General Studies courses which encompass the following components Islamic Civilization and Education, English and the third language, and curriculum.